Minimizing Fraud Behavior through Leadership Based on Tri Kaya Parisudha and Good Corporate Governance - Ida Ayu Putu Widani Sugianingrat; Putu Atim Purwaningrat; Luh Nik Oktarini; Ida I Dewa Ayu Yayati Wilyadewi (Faculty of Economics and Business Udayana University, 2021)
Fraudulent behavior can interfere with business continuity, therefore it needs to be minimized and even eliminated. This research tries to offer a solution to minimize fraudulent behavior through the implementation of leadership based on Tri Kaya Parisudha and Good corporate governance (GCG). The research was conducted at 94 Multipurpose Cooperatives in Bali. Research respondents were cooperative managers in each cooperative that was the research location. Data collection was carried out by distributing questionnaires to respondents via Google Form. The collected data will then be processed using the SmartPLS program. The results of hypothesis testing show that leadership based on Tri Kaya Parisudha has a significant positive effect on GCG, but has no significant effect on Fraud Behavior. On the other hand, GCG shows a significant negative effect on fraudulent behavior. Furthermore, GCG acts as a full mediator in the leadership relationship based on Tri Kaya Parisudha with Fraud Behavior.